Defense institution building in Africa : an assessment - McNerney, Michael J. (Michael Joseph) (Research report (Rand Corporation), 2016)
This report assesses U.S. efforts in defense institution building (DIB) in Africa and suggests possible improvements to planning and execution. It first defines DIB and reviews some best practices from DIB and security sector reform experiences. It also highlights how DIB activities serve U.S. official strategic guidance for Africa. The report then examines how DIB is currently planned and executed in Africa and describes the range of programs that are available to U.S. planners for that purpose. It also provides a structured approach to aid in the prioritization of such programs. The report then analyzes DIB efforts in two African nations--Liberia and Libya. Finally, it examines how other institutions and countries undertake DIB by taking a closer look at the DIB activities of DoD's regional centers, as well as the relatively extensive experience of two key U.S. allies--the United Kingdom and France--in this domain"--Publisher's description.